Improving the technical training of female athletes 10-11 years in rhythmic gymnastics in exercises with clubs - Alla Mullagіldіna; Inna Krasova (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to prove the expediency of using training combinations to increase the level of knowledge of young athletes with basic skills in exercises with clubs. Material & Methods: study was attended by nine athletes of 10-11 years old who train at the Children's and Youth Sports School of Rhythmic Gymnastics in the training group of the 2nd year of study. Using the method of expert evaluation and video analysis, the level of technical preparedness of athletes in the exercises with clubs and discounts for the technique of the subject in competitions was determined. Results: training combinations with clubs were developed, which consisted of exercises involving the combination of various technical work with the subject and body work with difficulty, as well as elements and connections from competitive programs. Conclusion: as a result of the introduction of training combinations, the discounts on the components of the equipment used by the object at competitions decreased: for performing "mills" - from 1,7 to 1,0 points; when making small throws and catching clubs - from 3,8 points to 2,7 points; in non-fundamental (non-specific) work - from 2,5 points to 1,7 points.